Design of Supercapacitor Electrodes Using Molecular Dynamics Simulations - Bo, Zheng; Li, Changwen; Yang, Huachao; Ostrikov, Kostya; Yan, Jianhua; Cen, Kefa (Nano-Micro Letters, 2018)
Electric double-layer capacitors (EDLCs) are advanced electrochemical devices for energy storage and have attracted strong interest due to their outstanding properties. Rational optimization of electrode–electrolyte interactions is of vital importance to enhance device performance for practical applications. Molecular dynamics (MD) simulations could provide theoretical guidelines for the optimal design of electrodes and the improvement of capacitive performances, e.g., energy density and power density. Here we discuss recent MD simulation studies on energy storage performance of electrode materials containing porous to nanostructures. The energy storage properties are related to the electrode structures, including electrode geometry and electrode modifications. Altering electrode geometry, i.e., pore size and surface topography, can influence EDL capacitance. We critically examine different types of electrode modifications, such as altering the arrangement of carbon atoms, doping heteroatoms and defects, which can change the quantum capacitance. The enhancement of power density can be achieved by the intensified ion dynamics and shortened ion pathway. Rational control of the electrode morphology helps improve the ion dynamics by decreasing the ion diffusion pathway. Tuning the surface properties (e.g., the affinity between the electrode and the ions) can affect the ion-packing phenomena. Our critical analysis helps enhance the energy and power densities of EDLCs by modulating the corresponding electrode structures and surface properties. Highlights: 1 Capacitive behaviors of electric double-layer capacitors (EDLCs) are strongly related to electrode geometry and electrode modification. 2 Molecular dynamics (MD) studies on EDLCs’ performances of electrode materials from porous to nanostructures are summarized. 3 MD could provide guidelines for the optimum design and fabrication of active materials.